Вы находитесь на странице: 1из 10

# ... 03.02.03.

5:
. ,
. , .
. .
( )

,
.
. .
( )

## : 5.1. . . . . . 5.2. . z-. . . . 5.3. z-. .

. 5.4. . . . . .

5.1. .
() ,
, ( ).

, . -
(),
.
z-
:
2
H(z) = H0+H1z+H2z +...= B(z)/[1+A(z)],
(5.1.1)
2
N
2
M
: B(z) = B0+B1z+B2z + ... +BNz , A(z) = A1z+A2z + ... +AMz .
, , A(z) B(z) H(z) z . z- (z),
:
Y(z) = H(z)(z) = X(z)B(z)/[1+A(z)],
Y(z)[1+A(z)] = Y(z)+Y(z)A(z) = X(z)B(z),
Y(z) = X(z)B(z)-Y(z)A(z).
(5.1.2)
z- (5.1.2)
:
N

n= 0

m =1

yk = bn xk-n am yk-m.

(5.1.3)

2
xk, yk k<0. . 5.1.1.
(5.1.3), k . 5.1.1. .
k-m, (m>0),
- . "" , , ,
. (-), , (-).

. B(z) .
-
, H(z)
(5.1.1).

, ..
.
.
. (z),B(z) H(z):
B (z) B2 (z) B N (z)
G 1
...
H(z)
=
,
A1 (z) A 2 (z) A N (z)
(5.1.4)
G - . ,
. 5.1.2, :
H(z) = G H1(z) H2(z) ..... HN(z),
Hn(z) = Bn(z)/An(z).
. 5.1.2. .
n(z) Bn(z)
( ):
2
Bn(z) = bn.0 + bn.1 z + bn.2 z ,
2
An(z) = 1 + an.1 z + an.2 z .
. H(z) :

H(z) = Ho(z)

Bn(z) / [1+An(z)],

n= 0

,
. 5.1.3. ,
, , ,
. 5.1.3. .

.

3
.
. , ,
, - ()
2
|H()| , .

5.2. .
(-)
. z-.
z-.

z- , . , ,
( ), :
H(z) = 1-z.
(5.2.1)
(5.2.1) zn1=1.
. 5.2.1,
H() i 0
N=/t - , (5.2.1), Vn1,
H(z) - n1
. 5.2.1. .
,
i - z(i) . i = 0 . - , 5.2.2 (5.2.1) , -.

. , (5.2.1)
:
H(z) = G(1-z)/(1-az), zp= 1/a.
(5.2.2)
, zp1=
1.01, =0,99.
G H(z) 1 . G=0.995. , t=1:
H(z) = 0,995(1-z)/(1-0.99z),
. 5.2.2. .
yk = 0.995(xk-xk-1)+ 0.99yk-1.
n1 1 z- .5.2.2. i Vn1(z) Vp1(z)
z(i) , :

4
|H(z)| = G Vn1(z)/Vp1(z).

. 5.2.0
Vn1(z) Vp1(z):
() = n1-p1.

v . 5.2.0.
z-. :
v = v/N.
(5.22.3)
(5.2.3) , -
( ), ..:
Hv(z) = G(z-zn)(z-zn*)/[(z-zp)(z-zp*)].
(5.2.4)
:
zn = cos v + j sin v = Re zn + j Im zn.
(5.2.5)
- R:
zp = Rcos v + j Rsin v = Re zp + j Im zp.
(5.2.6)
(n2 n2*) (2 2*) .5.2.1. (5.2.5-5.2.6) (5.2.4), :
G(z 2 2z Re z n + 1)
Hv(z) =
,
(5.2.7)
2
2
1 + (z 2z Re z p )/R
2

## G = [1+(1+2Re zp)/R ] / (2+2Re zn).

(5.2.7) :
G(b 0 + b1z + b 2 z 2 )
Hv(z) =
,
1 + a 1z + a 2 z 2

(5.2.8)
(5.2.7')

b0 = 1, b1 = -2Re zn, b2 = 1.
(5.2.9)
2
2
a1 = - (2Re zp)/R , a2 = 1/R .
, :
yk = G(xk+b1xk-1+xk-2) a1yk-1 a2yk-2.
(5.2.10)
fs = 50 , . t = 0.001 z-:
fN = 1/2t = 500 ,
= fs/fN = 0.1.
R = 1.01. :
zn = cos + j sin = 0.951 + 0.309 j,
zp = Rcos v + j Rsin v = 0.961 + 0.312 j.

5
G (5.2.8):
G = 0.99.
:
b1 = -2Re zn = -1.902,
a1 = - (2Re zp)/R2 = -1.883, a2 = 1/R2 = 0.98.

(5.2.7') z = exp(-j) ,
. 5.2.3:
0.99[1-1.902exp(-j)+exp(-2j)]
H() = ---------------------------------------------------------

1-1.883exp(-j)+0.98exp(-2j)
:
. 5.2.3.
yk = 0.99(xk - 1.902xk-1 + xk-2) + 1.883yk-1 0.98yk-2.
. 5.2.4 ,
50 53 , (
). . ,
.
50 .

. 5.2.4.

R 1 ,
, ,

.
(45)/(R-1). ,
, . 5.2.5.
. 5.2.5.
.
( ), G.
. (5.2.4) , , s ,
:
Hs(z) = G/[(z-zp)(z-zp*)],
(5.2.11)
G1
Hs(z) =
,
(5.2.11')
1 + a 1z + a 2 z 2

6
(5.2.11)
z- (. 5.2.1).
(, 2 2*)

. 5.2.6.
.
( z- )
( )
( 2), ( ) , ( s), . , Hs() s R 1
. ( G1=1) . 5.2.6. 1 G1 Hs() = 1 = s, ..:
G1 = 1+a1 z(s)+a2 z(s)2.
(5.2.11)

.
,
Hv(z):
Hs(z) = 1-Hv(z).
c + c z + c2z 2
.
(5.2.12)
Hs(z) = 0 1
1 + a 1z + a 2 z 2
0 = 1-G, c1 = a1-Gb1, c2 = a2-G.

. 5.2.7. . 5.2.7.
, ,
. 5.2.8.

. 5.2.8. .
(!!!KP30- ).
(!!!KP12- ).
(!!!KP13- ).
(!!!KP14-
).

5.3. z-.

7
z- ( ). ,
-
, z- z-. ,
. .
z , - .
. z-
:
z = exp(-pt),
(5.3.1)
t - , p , = +j.
(5.3.1) ln z = -pt ln z :
ln z = -2[(1-z)/(1+z)+(1-z)3/(3(1-z)3)+ ....], z > 0.
z- :
p = (2/t)(1-z)/(1+z).
(5.3.2)
, p-
z-, . :
p = (1-z)/(1+z),
(5.3.3)
z = (-p)/(+p).
(5.3.4)
, = 1. p = j (5.3.4) z :
z = r exp(j()), r = |z| = 1.
() = 2 arctg(/),
- () - (. . 5.3.1), ..
p- (p = j, - < < )
z-. :
= 0, z = exp(j0) = 1,
= , z = exp( j) = -1
. 5.3.1.
. (
)
- - +. z : - - -/t /t z-. , z-. (5.3.2) z = exp(-jt) -

8
exp(jt/2), :
p = (2/t)[exp(jt/2)-exp(-jt/2)] / [exp(jt/2)+exp(-jt/2)],
p = (2/t) th(jt/2).
(5.3.5)
- () , p
= j , th(x) = - jtg(jx), :
= (2/t) tg(t/2) = tg(t/2), -/t<</t.
(5.3.6)

. 5.3.2. .

(5.3.6)
, ,
p-, ,
,
-
, . . 5.3.2 (
).

5.4. .
, , . H() , - () .
() , , , . . .

, ,
.
, , (). ( - , - , - ) .

.

p - , s
. ,
p -
,
s
(
). . 5.4.1. .
p s . .
5.4.1. ,
.

( , ..),
.
. ,
:
2
|H(W)| = H(W)H*(W) = 1/(1+An(W)),
(5.4.1)
n(W) - n- , W - (, W = /p).
n(W) , : n(W) << 1
2

(
n, ).
(5.4.1) p-
- ,
:
N/ 2

## H(p) = G n(p), n-,

n= 1

G
H(p) =
p po

(5.4.2)

(N-1) / 2

n= 1

n(), n-,

n() :
2
n(p) = 1/[(p-pn)(p-pn*)] = 1/(p -2 anp+bn).

(5.4.3)

(5.4.4)

10
.
. -
(.5.4.2).
. (
)
,
(
. 5.4.2. .
) ( ).
( , ) .

## 12. .. . - .: , 1985.- 300 .

18. .. :
. - .: , 1986.- 342 .
24. .. . .: , 1987. 221 .
, : prodav@narod.ru.
.

## Нижнее меню

### Получите наши бесплатные приложения

Авторское право © 2022 Scribd Inc.